2018
DOI: 10.1007/s11695-018-3255-3
|View full text |Cite
|
Sign up to set email alerts
|

LSG vs MGB-OAGB—3 Year Follow-up Data: a Randomised Control Trial

Abstract: In our study, at 36 months follow up, there was no significant difference between LSG and MGB-OAGB in %EWL and remission of HTN. Type 2 diabetes mellitus (T2DM) remission rates were higher after MGB-OAGB as compared to LSG but the difference was statistically insignificant. MGB-OAGB patients with comorbidities have a better quality of life and BAROS score compared to LSG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Following systematic searches in MEDLINE, EMBASE and trial registries, 2291 abstracts were identified, and following exclusions, 25 articles regarding 20 RCTs (1803 patients) were included [ 35 – 59 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following systematic searches in MEDLINE, EMBASE and trial registries, 2291 abstracts were identified, and following exclusions, 25 articles regarding 20 RCTs (1803 patients) were included [ 35 – 59 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…At 2 years, 4 RCTs compared RYGB with SG, 2 RCTs compared RYGB v OAGB and 2 RCTs compared SG with OAGB [ 39 , 41 , 43 , 46 , 47 , 53 , 57 , 59 ] (Table 2 ). In standard meta-analysis, no approach was favoured over another for EWL at 2-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the efficacy and safety of OAGB have been validated [ 3 , 4 , 5 ] and its ability to control dyslipidemia has now been demonstrated [ 9 , 14 , 24 ], this approach is included in the ongoing debate on which procedure is the most effective in such patients. A moderate amount of studies focused on remission of T2DM, comparing OAGB with other surgical procedures [ 8 , 9 , 11 , 25 , 26 , 27 ]. Thus, this study attempts to compare LSG and OAGB in term of improvement of lipid profile in patients with severe obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery has become one of the most efficient methods for treating morbid obesity, not only because it dramatically reduces weight loss, but also by resolving associated comorbidity as well (4). Post-operative weight loss is also stimulated by the decreased production of hormones related to obesity such as ghrelin, which is vastly produced by the cells of the gastric fundus, the majority of which is removed during sleeve gastrectomy (SG).…”
Section: Introductionmentioning
confidence: 99%